Insulin‐resistance in glycogen storage disease type Ia: linking carbohydrates and mitochondria?. Issue 6 (12th February 2018) - Rossi, Alessandro; Ruoppolo, Margherita; Formisano, Pietro; Villani, Guglielmo; Albano, Lucia; Gallo, Giovanna; Crisci, Daniela; Moccia, Augusta; Parenti, Giancarlo; Strisciuglio, Pietro; Melis, Daniela
Abstract: Background: Glycogen storage disease type I (GSDI) is an inborn error of carbohydrate metabolism caused by mutations of either the G6PC gene (GSDIa) or the SLC37A4 gene (GSDIb). GSDIa patients are at higher risk of developing insulin‐resistance (IR). Mitochondrial dysfunction has been implicated in the development of IR. Mitochondrial dysfunction can demonstrate abnormalities in plama acylcarnitines (ACs) and urine organic acids (UOA). The aim of the study was to investigate the presence of mitochondrial impairment in GSDI patients and its possible connection with IR. Methods: Fourteen GSDIa, seven GSDIb patients, 28 and 14 age and sex‐matched controls, were enrolled. Plasma ACs, UOA, and surrogate markers of IR (HOMA‐IR, QUICKI, ISI, VAI) were measured. Results: GSDIa patients showed higher short‐chain ACs and long‐chain ACs levels and increased urinary excretion of lactate, pyruvate, 2‐ketoglutarate, 3‐methylglutaconate, adipate, suberate, aconitate, ethylmalonate, fumarate, malate, sebacate, 4‐octenedioate, 3OH‐suberate, and 3‐methylglutarate than controls (p < 0.05). GSDIb patients showed higher C0 and C4 levels and increased urinary excretion of lactate, 3‐methylglutarate and suberate than controls (p < 0.05). In GSDIa patients C18 levels correlated with insulin serum levels, HOMA‐IR, QUICKI, and ISI; long‐chain ACs levels correlated with cholesterol, triglycerides, ALT serum levels, and VAI. Discussion: Increased plasma ACs and abnormal UOA profile suggest mitochondrial impairment in GSDIa. Correlation data suggest a possible connection between mitochondrial impairment and IR. We hypothesized that mitochondrial overload might generate by‐products potentially affecting the insulin signaling pathway, leading to IR. On the basis of the available data, the possible pathomechanism for IR in GSDIa is proposed.